Observe to reflect: the (dis)engagement of a group of teachers in the (trans)formation of pedagogical practices. - Salgado,A.; Salustio,L.; Graça,T.; Martins, D. (I International Congress of Student Engagement in School: Perspectives of Psychology and Education Motivation for Academic Performance (IICIEAE), 2016)
The purpose of this communication is to present a different approach involving the experience of teachers of elementary and secondary education from different educational areas, such as Portuguese and Mathematics, in the classroom observations and reflection cycles concerning educational practices. These reflexive cycles are the background of the project “Projeto de Intervisão”, which was voluntarily implemented in Escola Secundária de Camarate. A group of teachers facing a multicultural student body, who has diversified socio-economic and family background and who is characterized by some inadequate behaviour and school failure, chose to get involved in a pilot study of cross-curricular lesson observation: a promoter not only of a reflective practice and of their professional development but also of the educational success of their pupils. Formed by twelve teachers from nine different areas, the group defined themselves as “Amigos Críticos” (Critical Friends). Underlying this denomination was the concept of “intervisão”, whose definition is connected with peer coaching strategies and competences for promoting professional collaboration, critical reflection, and democratic and regulatory teaching practices. Assuming itself as a sharing and collaborative practice of (self ) regulation, supported by peers with similar professional hierarchy, it assumes a great importance in the professional development as it implies moments of active learning and self regulation, allowing teachers to observe classes and being observed, achieving a feedback that promotes reflection and improves teaching practices. To implement the "Projecto de IntervisãoQ", the group attended training in different areas of management and classroom dynamics, having complemented their knowledge in supervision and evaluation of the impact of projects. The group developed practices for the observation of lessons through the conceptualization of the intervision and the construction of record grids. The intervision moments were operationalised in three stages: peer observation, reflection of the observation process, and peer and plenary sharing of the, the teachers shared experiences based 867 Atas do II Congresso Internacional Envolvimento dos Alunos na Escola: Perspetivas da Psicologia e Educação Motivação para o Desempenho Académico Lisboa: Instituto de Educação da Universidade de Lisboa, 2016 ISBN: 978-989-8753-35-9. in observation, identifying gains in a culture of sharing and previous reflection. The exchange of roles observing-being observed promoted a major reflective interaction. In plenary joint (re) construction of knowledge and materials used as a background to the implementation of the intervision From this experience it is highlighted the added value in its usage inside the same class, allowing the replication of classroom strategies/dynamics, inhibitors of disciplinary incidents and learning enablers. Thinking in terms of future time perspective, it is considered the construction of a guiding framework for the good teaching practices, using the output of the peer observations.